Analisis Landasan Epistemologis dalam Pengembangan Kurikulum Pendidikan Agama Islam di Sekolah Menengah Pertama - Guswantoro, Hari (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This study aims to investigate the role and influence of epistemological foundations in the development of the Islamic Religious Education (PAI) curriculum in junior high schools (SMP). The background of this research is based on the importance of the Islamic epistemological foundations in determining the validity and boundaries of knowledge within Islamic teachings, which is crucial to ensure the consistency and relevance of the PAI curriculum with the needs of students. This research employs a qualitative approach with a case study design involving document analysis and in-depth interviews as data collection techniques. The findings indicate that an understanding of the Islamic epistemological foundations influences the selection of learning materials, the development of teaching methods, and the integration of Islamic values in the PAI curriculum in SMP. The study also reveals challenges in the curriculum implementation, including differing interpretations of Islamic teachings, limited resources, and varying understandings of Islamic epistemology among teachers. The research concludes that a deep understanding of the Islamic epistemological foundations is a critical aspect in developing the PAI curriculum in SMP and requires collaborative efforts between educators, policymakers, and the Islamic community to overcome these challenges and ensure the effectiveness of Islamic religious education in schools. The implications of this study highlight the need for enhanced training and resources for teachers to strengthen the implementation of a curriculum based on the principles of Islamic epistemology.